Comparison of human coagulation factor VIII expression directed by cytomegalovirus and mammary gland-specific promoters in HC11 cells and transgenic mice - Wang, Qing (Blood Coagul Fibrinolysis, 2015)
Hemophilia A is an inherited X-linked recessive bleeding disorder caused by coagulant factor VIII (FVIII) deficiency. The conventional treatment involves the administration of recombinant human FVIII (rhFVIII) preparations. In this study, the mammary gland ‘bioreactor’ is designed to specifically and efficiently express a foreign protein hFVIII in the mammary glands of transgenic mice. We constructed a P1A3-hFVIIIBD vector directed by the mammary gland-specific P1A3 promoter, and transiently transfected HC11 cells and mouse mammary glands with P1A3-hFVIIIBD or CMV-hFVIIIBD vectors directed by a ubiquitous cytomegalovirus (CMV) promoter, respectively. We also generated P1A3-hFVIIIBD and CMV-hFVIIIBD transgenic mice by microinjection, respectively. Our data indicated that both vectors effectively expressed hFVIIIBD in HC11 cells at the transcription level, and hFVIIIBD protein was efficiently expressed in mouse milk after the injection of the hFVIIIBD vectors into mouse mammary glands during lactation. In both CMV-hFVIIIBD and P1A3-hFVIIIBD transgenic mice, hFVIIIBD proteins were efficiently expressed in the mammary glands at the mRNA and protein levels. No significant difference was observed in hFVIIIBD levels between the CMV-hFVIIIBD and P1A3-hFVIIIBD transgenic mice (P > 0.05). However, the activity of hFVIII in CMV-directed transgenic mice was slightly higher than that in P1A3-directed transgenic mice (P < 0.05). While hFVIIIBD was present in multiple organs in CMV-hFVIIIBD mice, P1A3-hFVIIIBD mice showed negligible hFVIIIBD expression in organs other than the mammary glands. This study demonstrated that the mammary gland-specific P1A3-hFVIIIBD vector was more suitable for the generation of hFVIIIBD mammary gland bioreactor.